Historical, theoretical methodological foundations of recreational activity of different population groups - Olena Andreeva (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to justify and develop historical, theoretical and methodological foundations of recreational activity to meet the recreational needs of different population groups. Material and Methods: analysis and systematization of the special scientific and methodological literature and informational Internet resources; comparative method, historical analysis; systemic approach. The study involved school and college students and adults, in total of 1150 persons. Results: historical backgrounds of formation and development of recreation in the world and Ukraine are analyzed. Theoretical generalization of certain concepts of motivation in the area of physical recreation is provided, as well as theoretical and organizational principles of leisure and recreation in foreign countries are discussed. Conclusions: historical backgrounds of development of knowledge about recreation are identified and conceptual approaches to development of the theoretical and methodological foundations of recreational activities of various population groups are determined.